Flexible Porous Piezoelectric Cantilever on a Pacemaker Lead for Compact Energy Harvesting. Issue 1 (6th September 2018) - Dong, Lin; Han, Xiaomin; Xu, Zhe; Closson, Andrew B.; Liu, Yin; Wen, Chunsheng; Liu, Xi; Escobar, Gladys Patricia; Oglesby, Meagan; Feldman, Marc; Chen, Zi; Zhang, John X. J.
Abstract: Self‐sustainable energy generation represents a new frontier to greatly extend the lifetime and effectiveness of implantable biomedical devices, such as cardiac pacemakers and defibrillators. However, there is a lack of promising technologies which can efficiently convert the mechanical energy of the beating heart to electrical energy with minimal risk of interfering with the cardiovascular functions. Here a unique design is presented based on existing pacemaker leads tailored for compact energy harvesting. This new design incorporates flexible porous polyvinylidene fluoride‐trifluoroethylene thin film within a dual‐cantilever structure, which wraps around the pacemaker lead with two free ends sticking out for harvesting energy from the heart's motion. Under various anchor methods of the lead, the maximum electrical output yields 0.5 V and 43 nA under the frequency of 1 Hz. It is found that adding a proof mass of 31.6 mg on the dual‐cantilever tip results in a 1.82 times power enhancement. The scalability of the design is also demonstrated, e.g., by connecting two such units in parallel, their simultaneous vibration can together contribute to energy conversion. Collectively, this study implies that sufficient electrical energy can be converted from the kinetic energy of a pacemaker lead especially at low frequencies to sustain operations. Abstract : A low profile, modular, and compliant thin film energy harvester is developed based on existing pacemaker leads, with minimal risk of interfering with the cardiovascular function. The porous piezoelectric cantilever aims at converting the kinetic energy of a pacemaker lead motion into an electrical power output for implantable biomedical devices.